A Practical Guide to Sigma-1 Receptor Positron Emission Tomography/Magnetic Resonance Imaging: A New Clinical Molecular Imaging Method to Identify Peripheral Pain Generators in Patients with Chronic Pain - Shen, Bin; Yoon, Daehyun; Castillo, Jessa; Biswal, Sandip (Seminars in Musculoskeletal Radiology, 2023)
Accurately identifying the peripheral pain generator in patients with chronic pain remains a major challenge for modern medicine. Millions of patients around the world suffer endlessly from difficult-to-manage debilitating pain because of very limited diagnostic tests and a paucity of pain therapies. To help these patients, we have developed a novel clinical molecular imaging approach, and, in its early stages, it has been shown to accurately identify the exact site of pain generation using an imaging biomarker for the sigma-1 receptor and positron emission tomography/magnetic resonance imaging. We hope the description of the work in this article can help others begin their own pain imaging programs at their respective institutions.
Keywords: pain diagnosis; sigma-1 receptor; nociception; positron emission tomography; radiotracer